Limitation of future radiation exposures from the present operation of nuclear fuel cycle intalallations - Beninson, Dan Jacobo (Organismo Internacional de Energía Atómica, 1982)
Fil: Beninson, Dan Jacobo Comisión Nacional de Energía Atómica; Argentina